Optical recording of signal-mediated protein transport through single nuclear pore complexes - Keminer, Oliver (The National Academy of Sciences, 1999)
Optical single-transporter recording, a recently established fluorescence microscopic method, was used to study the selective transport of proteins through single nuclear pore complexes (NPCs) of Xenopus oocytes. Recombinant proteins containing either a nuclear localization signal (import protein) or a nuclear export signal (export protein) were generated as transport substrates. To approximate in vivo conditions as closely as possible, a Xenopus egg extract was applied to the cytosolic side and a Xenopus oocyte nuclear extract to the nuclear side of the NPCs. It was found that protein transport through functionally isolated, “patched” NPCs depended on signal sequences, extracts, and metabolic energy, as in vivo. All NPCs were competent for both import and export. The transport direction was strictly determined by the transport signal, and at none of the conditions explored was the import protein exported or the export protein imported, even when the application sides of the extracts were reversed. The mean transport rates of the single NPC were ≈2 dimers/s for the import protein and ≈4 dimers/s for the export protein (≈15 μM substrate concentration, 22–24°C), in good agreement with in vivo rates estimated for mammalian cells by microinjection experiments. The study shows that optical single-transporter recording permits the analysis of membrane transport processes not previously accessible to single-transporter recording and thus provides additional possibilities for the elucidation of nucleocytoplasmic transport mechanisms.